Republic of Madagascar : Mitigating the Impact of the Crisis on Education - World Bank (Washington, DC, 2014)
This report reviews the tools and mechanisms which could contribute to offsetting the negative effects of the current crisis on primary school outcomes in Madagascar. In a context of rapid deterioration of key education indicators, including enrollment and survival, key education stakeholders are faced with the challenging task of identifying tools and mechanisms that may contribute to rapidly restoring access to education. While a variety of programs have been implemented in the past, limited evidence exists on their potential impact on key factors influencing school outcomes. In addition, given the limited domestic and international resources at the disposal of policy-makers, priorities need to be established that will focus on the most urgent and important aspects of the current situation. This report aims at providing key stakeholders in the sector with information on existing tools and mechanisms that could potentially be used to put a halt to the rapid decline of the sectors. The analysis also identifies interventions with a strong potential to offset the effects of the crisis over the short and medium term.